Melioidosis vaccines: recent advances and future directions - Sengyee, Sineenart; Weiby, Sarah B.; Rok, Ivory T.; Burtnick, Mary N.; Brett, Paul J. (Frontiers in Immunology, 2025)
Melioidosis, caused by the Gram-negative bacterium Burkholderia pseudomallei, is a severe infectious disease that is responsible for a significant amount of morbidity and mortality in endemic areas. While the majority of melioidosis cases occur in Southeast Asia, South Asia and Northern Australia, the disease is being increasingly recognized across tropical and subtropical regions worldwide. Due to diagnostic and treatment challenges as well as the potential misuse of B. pseudomallei as a biothreat agent, an effective vaccine is critically needed. Over the years, numerous different strategies have been explored to develop melioidosis vaccines. Based on the choice of protective antigens, many of the resulting candidates would also be predicted to provide some level of protection against Burkholderia mallei, the etiologic agent of glanders. In this review, we examine the different approaches that have recently been used to develop melioidosis vaccine candidates, highlighting both traditional and emerging vaccine platform technologies. Using these approaches, several promising melioidosis and glanders candidates have been identified with pre-clinical animal studies providing valuable insights into the immunogenic and protective capacities of these potential vaccines. Collectively, this review summarizes recent advancements in melioidosis vaccine research and highlights critical findings that will help guide a path toward the development of a safe, effective and affordable vaccine to combat disease caused by B. pseudomallei.